The link between the West African Ebola outbreak and health systems in Guinea, Liberia and Sierra Leone: a systematic review - Shoman, Haitham; Karafillakis, Emilie; Rawaf, Salman (Globalization and health, 2017)
An Ebola outbreak started in December 2013 in Guinea and spread to Liberia and Sierra Leone in 2014. The health systems in place in the three countries lacked the infrastructure and the preparation to respond to the outbreak quickly and the World Health Organisation (WHO) declared a public health emergency of international concern on August 8 2014. The aim of this study was to determine the effects of health systems' organisation and performance on the West African Ebola outbreak in Guinea, Liberia and Sierra Leone and lessons learned. The WHO health system building blocks were used to evaluate the performance of the health systems in these countries. A systematic review of articles published from inception until July 2015 was conducted following the PRISMA guidelines. Electronic databases including Medline, Embase, Global Health, and the Cochrane library were searched for relevant literature. Grey literature was also searched through Google Scholar and Scopus. Articles were exported and selected based on a set of inclusion and exclusion criteria. Data was then extracted into a spreadsheet and a descriptive analysis was performed. Each study was critically appraised using the Crowe Critical Appraisal Tool. The review was supplemented with expert interviews where participants were identified from reference lists and using the snowball method. Thirteen articles were included in the study and six experts from different organisations were interviewed. Findings were analysed based on the WHO health system building blocks. Shortage of health workforce had an important effect on the control of Ebola but also suffered the most from the outbreak. This was followed by information and research, medical products and technologies, health financing and leadership and governance. Poor surveillance and lack of proper communication also contributed to the outbreak. Lack of available funds jeopardised payments and purchase of essential resources and medicines. Leadership and governance had least findings but an overarching consensus that they would have helped prompt response, adequate coordination and management of resources. Ensuring an adequate and efficient health workforce is of the utmost importance to ensure a strong health system and a quick response to new outbreaks. Adequate service delivery results from a collective success of the other blocks. Health financing and its management is crucial to ensure availability of medical products, fund payments to staff and purchase necessary equipment. However, leadership and governance needs to be rigorously explored on their main defects to control the outbreak.